Calculation of Roadlighting Photometric Parameters Under Mesopic Conditions - Dubnička, Roman; Gašparovský, Dionýz; Barčík, Michal; Lipnický, Lukáš (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
At the present the mesopic photometry is hot topic in lighting engineering especially in the public lighting. The mesopic photometry is used in particular to consider roadlighting photometric parameters where mesopic vison is relevant to car drivers and pedestrians. Nowadays, works in the framework of the joint technical committee JTC001 at CIE is focused on mesopic photometry application. Within JTC001 there are two groups which are assigned to solve the stated problems. The first of them concerns fundamental problems on the processes of mesopic vision. e. g. Adaptation luminance, field of view, pupil diameter of the eye etc. The second group follows the results of the first group. It should provide practical solutions in the mesopic photometry. One of this topic is devoted to roadlighting calculations. Methodology of roadlighting calculations is laid down in the document CIE 140:2000 which is currently under revision at CIE Division 4 (TC 4-15). Calculations are still based on photopic vision, i. e. Photopic photometric quantities what disqualifies some innovative light sources mounted into luminaires which could be more efficient than traditional light sources if taking into account the mesopic conditions. It means that the old approach suppresses the usage of these luminaires because it does not consider appropriately the processes in the mesopic region where efficiency of the human eye is different. It depends on particular situation on the road and it is influenced by many other parameters. Therefore, new approach in the roadlight calculation emerged as a necessity for lighting engineers, who deal with roadlight, to consider mesopic conditions. Some preliminary results have been published in papers dealing with calculations based on the S/P ratio. This paper deals with roadlighting calculations assuming the mesopic photometry applied for various situations on the road with different roadlight luminaires and different light sources. Detailed analyses of possibilities how to use the mesopic photometry in practical calculations of photometric parameters of roadlighting for selected situations and luminaires are also presented in the paper..
Výpočet fotometrických veličin osvětlení komunikací při mezopických podmínkách
Keywords: Public lighting; Roadlighting calculation; Mesopic photometry